Effect of the volatile constituents isolated from Thymus albicans, Th. mastichina, Th. carnosus and Thymbra capitata in sunflower oil - Miguel, Maria Graça (2015)
The composition of essential oils isolated from Thymus albicans and Thymbra capitata collected in Algarve (Portugal), Th. mastichina collected in Algarve and Estremadura (Portugal) and Th. carnosus also collected in Algarve, during the flowering phase, was analysed by gas chromatography (GC) and GC coupled to mass spectrometry (GC-MS). The antioxidant capacity of the oils as well as some of their main components was determined by periodic evaluation of the peroxide values in sunflower oils stored at 60 degreesC. These peroxide values were compared to that of butylated hydroxytoluene (BHT) and control (without adding antioxidants) under the same experimental conditions. The oils of Th. albicans and Th. mastichina, collected in Algarve, were dominated by 1,8-cineole (68% and 45%, respectively), whereas linalool (52%) was the main component from the oils isolated from Th. mastichina collected in Estremadura. Carvacrol (68%) was the major component present in the oils of Thymbra capitata while borneol (18%), terpinen-4-ol (11%) and camphene (9%) were the major ones in the essential oil of Th. carnosus. The essential oils as well as some of their main components showed higher antioxidant capacity than that of the synthetic antioxidant BHT. At the end of the experiment (57 days), BHT showed a percentage of inhibition of 20%, while that of the essential oils ranged from 46% for Th. carnosus, to 59% for Th. mastichina collected in Estremadura.